Improving Visual Field Awareness among Collegiate Softball Athletes: A Randomized Trial - Diana R. Feldhacker; Whitney Lucas Molitor (康复学报)
Objective:The purpose of this study is to determine the efficacy of high-performance vision training on enhancing visual field awareness among collegiate softball athletes, as well as to compare effectiveness of results based on intervention type which consisted of DynavisionTM D2 or therapist-led non-machine vision training.Methods:Twenty-one athletes were randomized to two groups: Group A participated in DynavisionTM D2 training, and Group B participated in non-machine, therapist-led visual training. Each group engaged in vision training,15 minutes, twice weekly for six weeks, following a pre-established vision training protocol. After pretesting, a 2-week familiarization period allowed both groups to orient to the DynavisionTM D2 training device. Group-specific interventions included dynamic skill training framed in a cognitive and sensory approach. A Repeated Measures Analysis of Variance (ANOVA) was used to analyze changes in means across multiple observations (pretest, posttest, and follow-up testing) within-and between-subject factors (Groups A and B) to determine differences among DynavisionTM D2 quadrant and ring hits and speeds of reaction time. Parametric testing was used as data followed a normal distribution. Statistical significance was set at α≤0.05.Results:The study demonstrated that high-efficacy vision training was effective in improving the peripheral field awareness of collegiate softball athletes. This was demonstrated via mean hits and speeds within quadrants and rings of the Dynavision. Both Group A and B demonstrated statistically significant improvements in number of hits within quadrants 1,2, and 4 as well as rings 3,4, and 5. In addition, both groups demonstrated statistically significant improvements in speed within all quadrants and all rings. Therefore, both DynavisionTM D2 training and alternative vision training may be effective training methods to improve the visual field awareness and reaction time of an elite athletic population; however, the DynavisionTM D2 may be a more effective tool. There was a statistically significant difference between Group A and Group B, with Group A experiencing more significant improvements than Group B in number of hits in quadrants 2 and 4 and rings 2 and 3 as well as speeds within quadrants 1 and 2 and ring 2 and 5. Follow-up testing, completed in the absence of additional intervention, confirmed study results and skill retention at 1-and 2-month follow-ups.Conclusion:Peripheral vision contributes to sport performance, with implications on an athlete's reaction time, anticipation, and overall safety while on the field. Research indicates improvement of visual field awareness can be gained through use of the DynavisionTM D2, yet these studies primarily involve subjects with established field loss or post injury, rather than as a training method among well athletes. The results from this study demonstrate the adaptability of the visual system for those with normal field of vision.